Litterfall production of mangrove forest in the beach waters of Sepi Bay, West Lombok - YULIADI ZAMRONI; IMMY SUCI ROHYANI (Society for Indonesian Biodiversity, 2008)
Litterfall production of mangrove forest study was carried out in the beach water of Sepi Bay, West Lombok, from July to October 2007. The collection of litter was done every 10 days, and then the litter was dried at 75oC to constant weight and separated into leaves, reproduction organs, and wood part components. The total mangrove litter fall average was 2.71 g/m2/day or 9.9 ton/ha/year, with the leaf, reproduction organs, and branch components being 87.56%, 11.33% and 1.54%. Contribution of Rhizophora mucronata litter fall was 1.48 g/m2/day, R. apiculata 0.49 g/m2/day, Sonneratia alba 0.48 g/m2/day, R. stylosa 0.25 g/m2/day, and Aegiceras corniculatum 0.01 g/m2/day.Key words: mangrove, litterfall, Sepi Bay.